Optimizing hygiene and microbial aspect of paper recycling: a sustainable approach for environmental conservation: Optimizing hygiene and microbial aspect of paper recycling - Bahram Wlia , Ahmed; Majedi, Soma (Cellular and Molecular Biology, 2025)
This study explores microbial dynamics in paper recycling, emphasizing the significance of sustainable practices for environmental preservation. Samples were collected from various urban waste sources in Erbil city, Kurdistan Region, Iraq, including materials such as pizza boxes, cigarette packets, and coffee cups. Pure bacterial colonies were isolated using standard methods, and their morphological and physiological traits were characterized through biochemical tests. Identification of bacterial species followed established protocols. The study identified diverse bacterial species associated with paper waste, highlighting potential hygiene concerns in the recycling process. The findings of this study contribute to understanding the microbial ecology associated with paper waste and recycling processes. By optimizing hygiene measures and gaining insights into the microbial communities present, this research underscores the importance of sustainable practices in paper recycling to mitigate environmental impacts and promote a healthier ecosystem. Policies for future waste management and reduction of environmental risks have been proposed.